Restitution of cultural goods removed in the context of colonialism: an instrument of development and intercultural dialogue. (Cadernos de Sociomuseologia, 2014)
This article addresses the restitution of cultural property removed from the context of colonialism, the establishment of the international regime for the protection and restitution of cultural heritage, its principles, limitations and possibilities. Discusses the legitimacy of claims for restitution from the perspective of imprescriptibility crimes against Human Rights of the colonial period, and as a means for the decolonization of the relations between former colonies and former metropolis and reverse the effects of colonialism still present as the weaknesses of national identities of former colonies.Keywords: Restitution, Cultural properties, Development, Colonialism.